Flavia Kaba y Fernando Cid Lucas. Trampolín. Manual para aprender español a través de su literatura. Tirana: EDFA, 2024, 263 p. Recenzie de carte - Darius-Aurelian DRAGOMIR-COZMA (Eon)
In the age of digitalization, the instantaneous transmission and reception of information, and the essentialization of the message, teaching literature in the Spanish as a Foreign Language (ELE) classroom seems to pose ever more challenges for teachers. However, a teaching method like Trampolín: A Manual for Learning Spanish Through Literature, proposed by teachers Flavia Kaba and Fernando Cid Lucas, seems to make this task more enjoyable and even engaging. Through excerpts from classic or more recent literary works, the authors open the door to the study of Spanish literature and language, Hispanic culture and civilization, literary criticism, grammar, prosody, and paremiology through interactive and diverse teaching strategies. Through this proposed literary canon, the authors created a teaching ladder that allows students to advance from an A2 to a B1 proficiency level. Trampolín: A Manual for Learning Spanish Through Literature can serve as a support for a course in itself and as a complement to the Spanish curriculum at school and university.